Mexican experience in the implementation of the RothC-26.3 model of the dynamics of organic carbon in soils: scope and limitations - González-Molina, Lucila; Carrillo-Anzures, Fernando; Acosta-Mireles, Miguel; Báez-Pérez, Aurelio; Espitia-Rangel, Eduardo; Etchevers-Barra, Jorge D.; Paz-Pellat, Fernando (REVISTA TERRA LATINOAMERICANA, 2022)
The use of models of the dynamics of organic carbon in soils has been emphasized for the implementation of different public programs, including greenhouse gas inventories. The RothC 26.3 model (RothC) is one of the most used worldwide in the study of C dynamics. The objective of this study was to make a synthesis of the performance of the RothC model in predicting changes in SOC in plots, sites, systems and regions. As well as application in scenarios of land use change (LUC) and cropping systems using short-term (<20 years) databases and over a 40-year time period. In the plots the average initial SOCL (SOCinitial) was used by plot (CIPLOT) and SOCinitial at each sampling point (CIPT). The systems evaluated were agricultural, forestry, prairie and pasture. In the regions, the IPCC method was used and the RothC model method was used with partial information from the IPCC method. The simulation scenarios tested included LUC from traditional tillage to (i) agroforestry systems with castor, (ii) plantations of tropical tree species, and (iii) conservation tillage. LUC scenarios from secondary vegetation to tillage systems and scenarios with quinoa (Chenopodium quinoa) and amaranth (Amaranthus cruentus) crops were also tested. The results of the RothC model performance showed slightly better fit of the predictions when using CIPT, difficulty in modeling pastures and some tillage systems, and a high correlation between the methods used at the regional scale. Regarding the tested scenarios, the obtained trends and rates of SOC change coincided with estimations of other studies. In Mexico, it is necessary to consider the scope of the RothC model estimations of SOC changes based on its performance at different geographic scales, in different cropping systems and in different vegetation types.